The Architecture of Bahra 1, an Ubaid Culture-Related Settlement in Kuwait - Bieliński, Piotr (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
The Bahra 1 site is located in the Al-Subiyah desert, stretching along the north coast of Kuwait Bay, about 7km from the present coastline at the foot of a low sandstone ridge. The uncovered remains of the settlement cover an extensive area, at least 180m long and 60m wide. Only the easternmost fringe of the settlement was located on the east slope of the ridge, with the baulk of the structures occupying a flattish terrace that falls away to the south. Upon discovery, the architectural vestiges in the western part of the site protruded to the surface; in the eastern part, they were covered by a thick layer of sand dune.